2006
DOI: 10.1007/s10902-005-1915-1
|View full text |Cite
|
Sign up to set email alerts
|

Network Size, Social Support and Happiness in Later Life: A Comparative Study of Beijing and Hong Kong

Abstract: happiness, later life, network size, perceived support, social network,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(135 citation statements)
references
References 40 publications
9
116
0
7
Order By: Relevance
“…In the sample of children who are happy, it was showed that their ability to delay gratification are longer than children who are less happy [5], [6]. Other studies indicate that person who are happy have social support and social involvement greater than unhappy [7]- [9]. Happiness is also positively related to self-esteem [10].…”
Section: Introductionmentioning
confidence: 95%
“…In the sample of children who are happy, it was showed that their ability to delay gratification are longer than children who are less happy [5], [6]. Other studies indicate that person who are happy have social support and social involvement greater than unhappy [7]- [9]. Happiness is also positively related to self-esteem [10].…”
Section: Introductionmentioning
confidence: 95%
“…The former is seen more as the outcome of an evaluation process, while the latter as an outcome of positive experiences (Alexandrova 2005;Max and Markus 2006). Despite this difference, some researchers, notably from sociology and economics, tend to see happiness, subjective well-being, and life satisfaction as synonymous and interchangeable (Heylighen 1992;Veenhoven 1991Veenhoven , 1997Easterlin 2001Easterlin , 2005Kohler et al 2005;Chan and Lee 2006). Additionally, the predictors or components of happiness, life satisfaction, or subjective well-being tend to overlap whenever the term is used.…”
Section: Determinants Of Happinessmentioning
confidence: 99%
“…Ample evidence demonstrates that people are happier with better social support or more social involvement (Baumeister & Leary, 1995;Booth, 1992;Brim, 1974;Chan & Lee, 2006;Gundelach & Kreinar, 2004;Jopp & Rott, 2006;Kehle & Bray, 2003;Lane, 1994Lane, , 2000Lu, 1999;Lu, Shih, Lin, & Ju, 1997;Natvig, Albrektsen, & Qvarnstrom, 2003;Neto, 2001;North, Holahan, Moos, & Cronkite, 2008;Perneger, Hudelson, & Bovier, 2004;Ryuichi et al, 1999;Singh et al, 2004;Uchida, Norasakkunkit, & Kitayama, 2004). Happiness is positively associated with self-esteem (Baumeister, Campbell, Krueger, & Vohs, 2003), and self-esteem reflects belongingness (Leary & Baumeister, 2000).…”
Section: Social Supportmentioning
confidence: 99%